Prediction of the future need for institutional care in Finnish older people: A comparison of two birth cohorts - Salminen M.; Eloranta S.; Vire J.; Viikari P.; Viikari L.; Vahlberg T.; Lehtonen A.; Arve S.; Wuorela M.; Viitanen M. (S. Karger AG, 2022)
Background: More recent birth cohorts of older people have better physical and cognitive status than earlier cohorts. As such, this could be expected to diminish the need for institutional care. The prediction of the future need for institutional care provides essential information for the planning and delivery of future care and social services as well as the resources needed.
Objective: To predict the future need for institutional care among older Finnish people born in 1940. Methods: Representative samples of home-dwelling 70-year-olds from Turku, Finland were examined with similar methods in 1991 (those born in 1920) (n = 1,032) and in 2011 (those born in 1940) (n = 956). Predictors of institutionalization rates from the earlier 1920 cohort, together with data of sociodemographic factors, health, psychosocial and physical status, the need for help, and health behavior, were used to predict the future institutionalization rate among the 1940 cohort in this study using Cox regression models.
Results: Health as well as psychosocial and physical status were significantly better in the 1940 cohort compared to the earlier cohort. In the 1940 cohort, the predicted rates of institutionalization were 1.8, 10.4, and 26.0% at the ages of 80 (year 2020), 85 (year 2025), and 90 years (year 2030), respectively. At every age (80, 85, and 90 years), the predicted rates of institutionalization by Mini-Mental State Examination (MMSE) were about two-fold among those with MMSE scores 18-26 (3.0-38.8%) compared to those with scores 27-30 (1.6-23.7%) and those with a body mass index (BMI) <25 (2.5-34.3%) compared to those with a BMI of 25-29.9 (1.4-20.9%), and about three-fold among participants with several falls (5.3-57.0%) compared to participants with no falls (1.5-23.1%).
Conclusions: The 1940 cohort performed better in health as well as psychosocial and physical status than the 1920 cohort. Nevertheless, the predicted rates of future need for institutional care were high, especially at the ages of 85 and 90 years, among those with a lowered cognitive or physical status.